Leaf phenology and tree growth are uncoupled in three deciduous tree species - J.Julio Camarero; Álvaro Rubio-Cuadrado (Trees, Forests and People)
Climate warming is expected to lengthen the phenological season of deciduous broadleaf trees. Such longer phenological seasons could also lead to higher growth rates. This hypothesis was tested by examining and relating leaf phenology and tree-ring width series of three European deciduous tree species (Betula pendula, Fagus sylvatica, Quercus robur). Leaf onset and fall dates were used to define the duration of the phenological season. Leaf phenological variables were compared with climate and radial growth rates (basal area increment) obtained from nearby sites. This comparison was done in 17 sites located across a wide geographical gradient in Europe (7.12–87.80 °E, 46.14–66.37° N). In general, leaf emergence dates are advancing as spring temperatures rise. In most sites and species, growth variability, phenology (dates of leaf emergence and senescence) and the duration of the phenological season were not related. In the few sites where relationships between growth and phenology were found, they changed through time. These findings indicate that a longer phenological season does not entail higher growth rates in deciduous tree species. Climate warming may trigger an earlier start of the phenological season in some species, which may lead to longer phenological seasons, but not necessarily to enhanced radial growth rates and carbon sequestration in the form of woody tissues.